Study protocol of a co-created primary organizational-level intervention with the aim to improve organizational and social working conditions and decrease stress within the construction industry - a controlled trial - Emma Cedstrand; Anna Nyberg; Theo Bodin; Hanna Augustsson; Gun Johansson (BMC, 2020)
Abstract Background Within construction industry, physical work exposures have long been recognized as possible determinants for musculoskeletal disorders, but less attention has been given the increasing organizational and social work hazards and stress within this industry. There is to date a lack of knowledge about how to improve organizational and social working conditions and decrease stress within the construction industry. Methods This paper outlines the design of a controlled trial to evaluate the effectiveness of a co-created organizational-level intervention with the aim to improve role clarity, quantitative demands, staffing, planning, team effectiveness, psychosocial safety climate and stress. Two regions (> 700 employees) within one large construction company in Sweden will participate as intervention and control group. Further we present the design of the process evaluation assessing fidelity, support from managers, readiness for change and contextual factors. We will utilize questionnaires, semi-structured interviews, observations and documentation as means for data collection, hence a mixed methods approach is applied. Discussion The study is expected to contribute to the understanding of how adverse organizational and social working conditions and stress can be improved within the construction industry. By applying co-creation we wish to develop an intervention and implementation strategies that fit to the context, are in line with the needs of end-users and are supported by all management levels - all of which are highlighted features in successful workplace interventions. Trial registration ISRCTN, ISRCTN16548039 . Registered 12/02/20. Retrospectively registered